2002
DOI: 10.1080/01431160110092885
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between macrophyte stand variables and radar backscatter at L and C band, Tucuruí reservoir, Brazil

Abstract: Information on macrophyte distribution in space and time is very important for tropical reservoir management. Macrophyte stands are major sinks/ sources of methane and the knowledge of their spatial and temporal variation in biomass is useful for improving the assessment of the role of reservoirs in the carbon cycle. Moreover, macrophyte stands are a driving force in insect-induced diseases such as malaria. In this paper we examine the relationship between macrophyte stand variables such as above-ground biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…However, further research and development is needed to quantify not only the difference in vegetation versus no vegetation, but also how different resolutions, bands, and angles of radar reflect off different vegetation types, densities, and heights. It has been suggested that C-band imagery should be used when trying to map leaf shape and that L-band is more accurate for measuring aboveground biomass and stand height [98]. Other research has demonstrated that a multi-temporal and multi-incidence angle was the best approach, with steep incidence angles for mapping wetlands and large incidence angles for detecting open water from land [99][100][101].…”
Section: Resultsmentioning
confidence: 99%
“…However, further research and development is needed to quantify not only the difference in vegetation versus no vegetation, but also how different resolutions, bands, and angles of radar reflect off different vegetation types, densities, and heights. It has been suggested that C-band imagery should be used when trying to map leaf shape and that L-band is more accurate for measuring aboveground biomass and stand height [98]. Other research has demonstrated that a multi-temporal and multi-incidence angle was the best approach, with steep incidence angles for mapping wetlands and large incidence angles for detecting open water from land [99][100][101].…”
Section: Resultsmentioning
confidence: 99%
“…Results from this analysis suggest that, although an acceptable accuracy can be achieved with Landsat and a DEM alone, the SAR variables are important for improving the class accuracy of bog and fen. It may also be possible to achieve higher classification accuracies with only SAR variables and a DEM if multiple SAR images acquired across different dates [68][69][70][71], incidence angles [72][73][74], and moisture conditions [75] are combined as inputs to the classifier. In some cases, classification accuracy can increase significantly [75].…”
Section: Variable Importancementioning
confidence: 99%
“…This attribute of SAR was first noticed with Seasat data (MacDonald et al 1980) and is a wellknown capability of SAR (Hess et al 1990). The sensitivity to the target's moisture content and structural differences in the types of wetland vegetation also provide a capability for mapping wetlands (Pope et al 1994, Brisco and Pultz 1998, Novo et al 2002 especially when combined with optical data (Wang et al 1998, Toyra andPietroniro 2005). This is described in more detail in the next section.…”
Section: Flood and Flooded Vegetation Monitoringmentioning
confidence: 99%
“…SAR interferometry at C-band has also been successfully used for delineating flooded and non-flooded regions (Morley et al 1996). Research has shown that a multi-frequency combination is preferred, such as L and C-band, which can provide discrimination between a larger number of wetland vegetation types including flooded forest and aquatic macrophytes (Costa et al 2002, Novo et al 2002.…”
Section: Flood and Flooded Vegetation Monitoringmentioning
confidence: 99%